Graft Selection in Anterior Cruciate Ligament Reconstruction. Issue 2 (June 2020) - Lin, Kenneth M.; Boyle, Caroline; Marom, Niv; Marx, Robert G.
Abstract : Surgical reconstruction of the anterior cruciate ligament (ACL) is often indicated to restore functional stability and prevent early degeneration of the knee joint, as there is little biological healing capacity of the native ACL. Although a reconstructed ACL does not fully restore the original structure or biomechanics properties of the native ACL, the graft used for reconstruction must not only have structural and mechanical properties that closely resemble those of the native ligament, it must also have minimal antigenicity and enough biological potential to incorporate into host bone. There are several considerations in graft selection: autograft versus allograft, and soft tissue grafts versus grafts with bone plugs. Commonly used grafts include bone-patella tendon-bone, hamstring, and quadriceps; among allografts, options further include tibias anterior and posterior, Achilles, an peroneal tendons. Optimal graft selection is not only dependent on graft properties, but perhaps more importantly on patient characteristics and expectations. The purpose of this review is to summarize the relevant biological, biomechancial, and clinical data regarding various graft types and to provide a basic framework for graft selection in ACL reconstruction.